News Values in Slovak Television News - Ľuboš Greguš; Juliána Mináriková (Communication Today, 2025)
Television news – and journalistic information included in it – may be rightfully seen as one of the main constitutional elements of journalism. Considering contemporary conditions of the globalised information society, diversity of information sources and pluralism related to information dissemination, we have to focus mainly on media content associated with journalistic products. The text aims to deal with news values – more specifically, with their occurrence and application in the context of evening (main) TV news programmes which are broadcast by Slovak nationwide broadcasters. The theoretical part of the article discusses related media theories and basic normative demands that are linked to creative journalistic work. The authors also place emphasis on various definitions of news values and discuss them from the viewpoints of journalism and newsmaking development and also in terms of technological improvements related to contemporary mass media communication. Besides offering an overview on the theoretical outlines of the given topic, the authors aim to present results of own research. The inquiry was conducted in order to address the issue of news values associated with TV news contents created by selected commercial and public broadcasters. The research is based on the method of quantitative content analysis. In total 1120 TV news contributions were analysed during three deliberately selected weeks – their overall length reached 32 hours 32 minutes and 34 seconds. The research results helped the authors to better understand the current trends in news-making – i.e. the implementation of news values as well as quality, balance and relevance of the news content mediated through evening TV news programmes.